GATA2 mitotic bookmarking is required for definitive haematopoiesis - Silvério-Alves, R; Kurochkin, I; Rydström, A; Vazquez Echegaray, C; Haider, J; Nicholls, M; Rode, C; Thelaus, L; Lindgren, AY; Ferreira, AG; Brandão, R; Larsson, J; et al. (Springer Nature, 2023)
In mitosis, most transcription factors detach from chromatin, but some are retained and bookmark genomic sites. Mitotic bookmarking has been implicated in lineage inheritance, pluripotency and reprogramming. However, the biological significance of this mechanism in vivo remains unclear. Here, we address mitotic retention of the hemogenic factors GATA2, GFI1B and FOS during haematopoietic specification. We show that GATA2 remains bound to chromatin throughout mitosis, in contrast to GFI1B and FOS, via C-terminal zinc finger-mediated DNA binding. GATA2 bookmarks a subset of its interphase targets that are co-enriched for RUNX1 and other regulators of definitive haematopoiesis. Remarkably, homozygous mice harbouring the cyclin B1 mitosis degradation domain upstream Gata2 partially phenocopy knockout mice. Degradation of GATA2 at mitotic exit abolishes definitive haematopoiesis at aorta-gonad-mesonephros, placenta and foetal liver, but does not impair yolk sac haematopoiesis. Our findings implicate GATA2-mediated mitotic bookmarking as critical for definitive haematopoiesis and highlight a dependency on bookmarkers for lineage commitment.